Preeclampsia Risk in Bali, Indonesia: The Role of Maternal Body Mass Index (BMI) and Gestational Weight Gain (GWG) - I Gede Wara Nugraha; Rini Martina Siallagan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Preeclampsia, a hypertensive disorder of pregnancy, significantly contributes to maternal and infant mortality and morbidity globally, including in Indonesia. Pre-pregnancy obesity and excessive gestational weight gain (GWG) are established risk factors for preeclampsia. This study investigated the association between pre-pregnancy body mass index (BMI) and GWG with the incidence of preeclampsia in Bali, Indonesia. Methods: A case-control study was conducted at a Maternal Hospital in Bali, Indonesia, from May 2023 to May 2024. The study included 429 pregnant women: 143 with preeclampsia (cases) and 286 without (controls). Data were collected from medical records. BMI was categorized using Asia-Pacific criteria, and GWG was assessed based on the 2009 Institute of Medicine (IOM) guidelines. Logistic regression analysis was performed to determine the associations, adjusting for maternal age, education, and occupation. Results: Obesity class II (BMI ≥ 30 kg/m²) and obesity class I (BMI 25.0-29.9 kg/m²) were significantly associated with an increased risk of preeclampsia, with adjusted odds ratios (AOR) of 2.90 (95% CI: 1.19-7.08) and 2.78 (95% CI: 1.60-4.81), respectively, compared to women with normal weight. Excessive GWG was also significantly associated with preeclampsia (AOR 2.53; 95% CI: 1.48-4.33) compared to adequate GWG. Conclusion: Maternal obesity and excessive GWG are significant risk factors for preeclampsia in Bali, Indonesia. These findings underscore the importance of pre-pregnancy counseling and interventions to manage weight and promote healthy GWG to reduce the burden of preeclampsia.